Capturing the Cry of Flood Victim Students: An Exploration of their Experience and Resilience through Photovoice - May Noren D. Nanud; Angelyn T. Caylan; Jessel C. Lagura; Genelyn R. Baluyos (PT ARRUS Intelektual Indonesia, 2023)
Floods greatly impact individuals, especially vulnerable students, affecting them psychologically, socially, and academically. This study explored the experiences of student flood victims and uncover their resilience through the innovative methodology of photo voice. Two participants who were selected through snowball purposive sampling. Data were collected through photos and interviews. The themes emerged from the experiences of students who have been affected by floods were having unstable emotions, undergoing academic strain, and wanting to be heard. Also, the themes emerged from the flood-affected students’ perception and coping mechanisms with the challenges they face in the aftermath were seeking for support and using of varied coping mechanisms. This study shed light on the psychosocial effects of flooding on student victims, highlighting their resilience in the face of adversity. Flood – affected students resiliently seek support for their needs, employ diverse coping mechanisms, and desire recognition from authorities and institutions amidst emotional instability, academic obstacles, and the impact of significant losses caused by floods. School administration and LGU officials collaborate to establish a dedicated disaster risk and reduction management office to provide prompt response and assistance to flood-affected students. Additionally, it is important to implement emotional support programs, prioritize the allocation of academic resources and support, and actively promote student engagement.